A Major Cell Surface Antigen of Coccidioides immitis Which Elicits Both Humoral and Cellular Immune Responses - Hung, Chiung-Yu (American Society for Microbiology, 2000)
Multinucleate parasitic cells (spherules) of Coccidioides immitis isolates produce a membranous outer wall component (SOW) in vitro which has been reported to be reactive with antibody from patients with coccidioidal infection, elicits a potent proliferative response of murine immune T cells, and has immunoprotective capacity in a murine model of coccidioidomycosis. To identify the antigenic components of SOW, the crude wall material was first subjected to Triton X-114 extraction, and a water-soluble fraction derived from this treatment was examined for protein composition and reactivity in humoral and cellular immunoassays. Protein electrophoresis revealed that the aqueous fraction of three different isolates of C. immitis each contained one or two major glycoproteins (SOWgps), distinguished by their molecular sizes, which ranged from 58 to 82 kDa. The SOWgps, however, showed identical N-terminal amino acid sequences, and each was recognized by sera from patients with C. immitis infection. Antibody raised against the purified 58-kDa glycoprotein (SOWgp58) of the Silveira isolate was used for Western blot and immunolocalization analyses. Expression of SOWgp was shown to be parasitic phase specific, and the antigen was localized to the membranous SOW. The water-soluble fraction of SOW and the purified SOWgp58 were tested for the ability to stimulate proliferation of human peripheral monocytic cells (PBMC). The latter were obtained from healthy volunteers with positive skin test reaction to spherulin, a parasitic-phase antigen of C. immitis, and from volunteers who showed no skin test reaction to the same antigen. The SOW preparations stimulated proliferation of PBMC from skin test-positive but not skin test-negative donors, and the activated cells secreted gamma interferon, which is indicative of a T helper 1 pathway of immune response. Results of this study suggest that SOWgp is a major parasitic cell surface-expressed antigen that elicits both humoral and cellular immune responses in patients with coccidioidal infection.